2003
DOI: 10.1097/00005537-200310000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of endoscopic sinus surgery in patients with nasal polyps and asthma

Abstract: ESS demonstrates a beneficial effect on the sinonasal and asthma symptomatology in patients with nasal polyps and asthma using objective measures. Subset of aspirin-tolerant patients have statistically better outcome for sinonasal symptoms and pulmonary function testing than aspirin-sensitive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(110 citation statements)
references
References 12 publications
7
96
0
7
Order By: Relevance
“…Similar results have been reported by Batra et al (2003), which analysed 17 patients with nasal polyps and bronchial asthma as well as nine patients with ASS-intolerance and bronchial asthma, showing the improvement of bronchial asthma independent of ASS intolerance [19].…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been reported by Batra et al (2003), which analysed 17 patients with nasal polyps and bronchial asthma as well as nine patients with ASS-intolerance and bronchial asthma, showing the improvement of bronchial asthma independent of ASS intolerance [19].…”
Section: Discussionsupporting
confidence: 85%
“…However, symptom profiles differed between the two disease phenotypes, with headache and sleep disturbance being more present in CRSsNP while loss of sense of smell was more bothersome in CRSwNP using VAS scores and EPOS control criteria 17,18.…”
Section: Discussionmentioning
confidence: 99%
“…319,861,862 Using objective and subjective sinonasal and asthma outcome measures, studies have demonstrated significant clinical improvement following ESS. 320,861,[863][864][865][866] In patients with asthma and NPs, ESS was shown to improve asthma severity scores, reduce the need of inhaled corticosteroids and reduce the frequency of asthma-related emergency room visits. 863 Ehnhage et al 864 showed in a prospective randomized trial that patients with CRSwNP had a significant improvement in nasal and lower airway symptoms after ESS.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%